2019
DOI: 10.3390/ani9121156
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in Horses Kept in A 2.5 Year-Round Grazing System in Nordic Conditions without Supplementary Feeding

Abstract: Horse grazing can be favorable from a biological diversity perspective. This study documented the occurrence of endo- and ectoparasites and sought to reduce parasite egg excretion with the anthelmintic drug pyrantel in 12 Gotlandsruss stallions maintained in a year-round grazing system for 2.5 years. Feces samples were collected monthly and all horses were treated with pyrantel, the anthelmintic drug of choice in biological diversity preservation, at study population mean cyathostomin eggs per gram (EPG) of &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Repeatable observations of relatively high amounts of strongyle ova in feces of regularly dewormed animals may result, in addition to the aforementioned cessation of biological activity of ivermectin, from the development of the drug-resistance in representatives of Strongylidae. The latter, in turn, may be an outcome of incorrect use of the named anthelmintics [10,12]. This assumption is partly supported by already cited results by Kuzmina et al [38], who revealed that a statistically significant difference in EPG values was present only between horses with rare to lack of anthelmintic treatments but not between horses dewormed 1-2 a year vs. 3-4 times or more with macrocyclic lactones.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Repeatable observations of relatively high amounts of strongyle ova in feces of regularly dewormed animals may result, in addition to the aforementioned cessation of biological activity of ivermectin, from the development of the drug-resistance in representatives of Strongylidae. The latter, in turn, may be an outcome of incorrect use of the named anthelmintics [10,12]. This assumption is partly supported by already cited results by Kuzmina et al [38], who revealed that a statistically significant difference in EPG values was present only between horses with rare to lack of anthelmintic treatments but not between horses dewormed 1-2 a year vs. 3-4 times or more with macrocyclic lactones.…”
Section: Discussionmentioning
confidence: 79%
“…This procedure only temporarily reduces the number of adult parasites susceptible to the drug used [3]. The latter, combined with a recurrent application of the same and/or close pharmacological agents, with ivermectin and praziquantel being most commonly used [4][5][6] leads to partial or complete resistance developed by many parasites, especially gastro-intestinal, which cannot be eradicated with these drugs anymore [7][8][9][10][11][12]. The parasites that have become or have been gradually becoming resistant to currently used preparations are representatives Agriculture 2021, 11, 525 2 of 13 of Ascarididae, Strongylinae, Cyathostominae, Anoplocephalids and botflies from Gasterophilus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade two British studies have been published, with one finding similar seasonal egg shedding patterns [ 19 ], while the other found no evidence of such seasonality among adult horses [ 20 ]. Recently, a Swedish 2.5-year study of free-ranging ponies found strongylid fecal egg counts (FECs) to peak in August/September [ 21 ], and a New Zealand study reported broodmares to exhibit lower strongylid FECs during winter months [ 22 ], both confirming Poynter’s observations from almost 70 years ago. One study performed in ponies in Louisiana, USA, reported significantly lower mean strongylid FECs during winter months, but these were data from ponies that were euthanized at different time points, and repeated measures were not done across seasons [ 23 ].…”
Section: Introductionmentioning
confidence: 76%
“…During the study period, four individuals were temporarily removed due to low body condition in late winter. They were additionally dewormed when necessary using predefined indicators (Tydén et al 2019 ) and were provided with artificial shelter and water in troughs (one per enclosure according to national regulations). From January 2016, one horse was excluded from the study due to injury.…”
Section: Methodsmentioning
confidence: 99%